Developing a method for collecting and analysing data on board composition and compensation using a sample of Southeast Asian companies, School of Management - Mirzaev, Muzaffar P.; Venkatesh, Sundar; Sununta Siengthai; Badir, Yuosre; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Soon after Asian Financial Crisis in 1997 hit South East Asian countries partially due to weak corporate governance over companies, governments in the region with the practical guidelines of international development organizations such as Organization for Economic Co-operation and Development (OECD) and IMF, enacted their respective Corporate Governance (CG) codes. Some of the objectives of the codes are to improve board of director oversight and to disclose more transparent information to shareholders in particular and to stakeholders in general by providing detailed information on the structure of the Board of Directors (board) and remuneration, on which board members are being paid. The project explored the composition and compensation of board of the largest companies in five South East Asian (SEA) Countries. It examined the related rules and regulation of the selected countries. The results show that though the selected countries are different in terms of CG practices, the top companies of these countries are converging in terms of composition and compensation. There is also evidence that top companies in a country with low CG score have the board with better CG criteria than countries with high CG score. This method using comparative study starts with an overview of some CG principles, which is recommended by OECD and examines how these principles are being applied in SEA countries such as Indonesia, Malaysia, Philippines, Singapore, and Thailand, then proceeds by comparing main principles of CG codes used in such countries. Later, it discusses comparative study findings regarding, two specific features of corporate governance- board composition and compensation, which are currently being practiced by sample of 50 listed companies, 10 from each countries measured based on size. Finally, method on how to manage and organize data collection on board composition and compensation in the form of database, using Microsoft Excel spreadsheet is presented, which can be used further by analysts and researchers
A project study submitted in partial fulf illment of the requirements for the degree of Master of Business Administration in Business Administration
Project (M.B.A.) - Asian Institute of Technology, 2009
Keywords: Boards of trade -- Southeast Asia; Compensation management -- Southeast Asia